Nucleocytoplasmic localisation of extradenticle protein is spatially regulated throughout development in Drosophila. - Aspland, S.E.; White, R.A. (Development, 1997)
The extradenticle protein is a homeodomain transcription factor which has an important role regulating the DNA-binding specificity of homeotic selector proteins. We have made a monoclonal antibody against extradenticle and have studied the expression of the protein in the embryo and in imaginal discs. We find that extradenticle is initially uniformly distributed as expected but strikingly is excluded from nuclei until gastrulation. During the extended germ band stage the protein remains predominantly cytoplasmic and does not accumulate in nuclei until germ band retraction. Nuclear accumulation occurs in a highly spatially regulated pattern. In the imaginal discs the nuclear accumulation of extradenticle is also spatially regulated and, in the wing and leg discs, distal regions exhibit cytoplasmic extradenticle whereas proximally the protein is nuclear. We suggest that this regulation of the sub-cellular localisation of extradenticle is important for the interactions between extradenticle and the homeotic selector proteins and that extradenticle is not simply a ubiquitously available cofactor.